Urban Renewal and Sustainable Development Efforts in Montreal: Vitality and Multiculturalism Requirements from an Identity Protection Perspective - Viola, Serena (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2008)
An Italian researcher, sponsored by the Canadian Studies Faculty Research Program of Canadian Foreign Affairs, investigated the social, economic, and developmental consequences of the urban and architectural renewal initiatives undertaken in Montreal during the last ten years. The study looked at the satisfaction levels of new users of outdoor squares and walkways to evaluate the effectiveness of the preservation, promotion, and integration processes applied to public spaces in response to the challenges of creating a pedestrian culture reflective of contemporary vitality and multiculturalism. Traditionally, open spaces have helped shape the identity of built environments from a technical and constructive perspective while taking into account social and economic dynamics. A review of written documents on the evolution of Montreal's urban spaces suggests that the built environment has become a development driver in the active progress of identity preservation. The squares and walkways, the two elements that epitomize the community's heritage and symbolize its identity, were studied in order to unearth their cultural and imagery value and to understand how they combine individual interests with social values.